TEACHERS’ PERSPECTIVES ON PROJECT-BASED LEARNING INTEGRATED WITH ESD-STEM IN TEACHING PHOTOSYNTHESIS TO FOSTER CRITICAL THINKING - Lusi Ayu Gustari; Ghullam Hamdu (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study was motivated by the need for science education that can develop critical thinking skills in elementary school students through a contextual and sustainable approach. The integration of Project-Based Learning (PjBL), Education for Sustainable Development (ESD), and STEM is seen as a relevant innovative strategy, but its implementation in the field has not been fully structured. This study aims to analyze teachers' perspectives on the application of ESD-STEM integrated PjBL in photosynthesis learning and to examine its implications for the development of students' critical thinking skills. The research used a qualitative approach with an instrumental case study design conducted in three public elementary schools in Bungursari District, Tasikmalaya City. Data were obtained through in-depth interviews, learning observations, and documentation studies, then analyzed through a process of reduction, categorization, and thematic interpretation. The results showed that teachers had implemented project-based learning that encouraged active student involvement and fostered problem identification, cause-and-effect analysis, and data-based conclusion drawing skills, although the integration of ESD and STEM was still implicit and not yet fully systematic. This study concludes that the development of structured and reflective PjBL-ESD-STEM integrated teaching modules is necessary to optimize the development of students' critical thinking in sustainability-based science learning.